Rice husk ash based cementitious material for concrete canoe. Issue 6 (August 2020) - Pradeep, S; Deepak, P; Dheepak, S
Abstract: This article study about the properties of light weight concrete canoe using Rice husk ash, micro-silica and microsphere. Rice husk ash, an industrial by-product from boilers for parboiling rice, has been exposed as admixture to replace part of cement in structural mortar. Micro silica addition improves mechanical and durability behaviour in mortars. A microsphere is a lightweight, inert, hollow sphere made largely of silica and alumina and filled with air or inert gas, typically produced as a by-product of coal combustion at thermal power plants. In addition, as the rice husk ash comes from agricultural waste resources their use as secondary raw material will contributes to circularity in the economy. Parametric design of the hull form and internal arrangement of single rower canoe is designed. The Hull Design and stability analysis is done using MAXSURF software. Heel angle was targeted to achieve 60 degree and it had achieved up to 89 percentage. Strength analysis is carried out for the designed hull and then analysed. After finalized the mix design and the hull design, the mould is prepared. Finally, the canoe is casted and tested for stability.